Elementary School Teachers’ Training Needs: Innovating Digital Competence - Yudin Citriadin; Mohammad Viktor Farid Hakim (STAI Hubbulwathan Duri, 2021)
The purpose of the study was to determine the training needs needed by teachers in making digital products to facilitate the learning process. Training is as a way for teachers to innovate digital competencies. The participants of this study were 10 elementary school teachers (F=6 and M=4). Participants are homeroom teachers from grades 1 to 6, and 4 were subject teachers (Mathematics, English, local content and sports). This study used the descriptive qualitative method. Observation, documents and interviews collected data. The data analysis process used the Miles and Huberman model through data reduction, data presentation, drawing conclusions and triangulation. The results show that teachers need workshops that can directly practice making digital teaching tools such as learning videos and developing videos on the YouTube channel. However, they have difficulties with the technological devices they have. There are 30% of teachers who have full technology equipment, and the rest rely on smartphones for online teaching and learning. Thus, schools can consider providing technology tools that teachers can use in developing digital competencies and digital learning tools.